Eficiência da própolis verde no controle de helmintos gastrointestinais de cordeiros - Menezes, Bruna Martins de (2022)
The objective was to evaluate the efficiency of green propolis extract in the control of worms in Dorper x Santa Inês crossbred lambs in feedlots. Worms are the main health problem of small ruminants, causing economic and productive losses, such as weight loss, retarded development, infertility, death in severe cases, among others. The indiscriminate use of chemical products has caused them to lose their effectiveness. Thus, the search for natural products has increased, and green propolis, for presenting in its composition phenolic components, with antioxidant, immunomodulatory, antifungal and antibacterial activity, is an important contributor to these characteristics. The treatments were divided into: control: bidistilled glycerin in a single dose; the drug: single dose of Zolvix according to the directions on the package insert; the phytotherapeutic single dose: 0.3g of green propolis extract per body weight; and the phytotherapeutic two doses: 0.3g of propolis extract per body weight on days 0 and 30. The experiment was carried out in an entirely randomized design with four treatments and eight repetitions (animals). Five animals were randomly selected for the blood tests. The propolis extract was processed in four stages, namely dilution in a bain marie, filtration using a vacuum pump, rotoevaporation, and lyophilization. The animals were examined for reduction of eggs in feces, eggs per gram of feces, larval cultures, weighing, body condition score, FAMACHA©, hemogram and biochemical parameters on days 0, 15, 30, 45, 60 and 90. The extract of green propolis was not efficient in controlling worms; however, the animals remained healthy throughout the experimental period, which demonstrates a possible immunomodulatory action of this product, since even though they were parasitized, they were not harmed by the worms.